High prevalence of pre-existing serological cross-reactivity against severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) in sub-Saharan Africa. (January 2021) - Tso, For Yue; Lidenge, Salum J.; Peña, Phoebe B.; Clegg, Ashley A.; Ngowi, John R.; Mwaiselage, Julius; Ngalamika, Owen; Julius, Peter; West, John T.; Wood, Charles
Highlights: Cross-reactivity vs. SARS-CoV-2 high in sub-Saharan Africa pre-pandemic samples. Reactivity against other human coronaviruses high in pre-COVID-19 pandemic plasma. Other coronaviruses may have induced cross-reactive antibodies against SARS-CoV-2. Abstract: Objective: Significant morbidity and mortality have occurred in the USA, Europe, and Asia due to severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), whereas the numbers of infections and deaths in sub-Saharan Africa (SSA) have remained comparatively low. It has been hypothesized that exposure of the population in SSA to other coronaviruses prior to the COVID-19 pandemic resulted in some degree of cross-protection against SARS-CoV-2 infection and pathogenesis. We evaluated this hypothesis by comparing SARS-CoV-2 cross-reactive antibodies in pre-pandemic plasma samples collected from SSA and the USA. Method: Pre-COVID-19 pandemic plasma samples from SSA and the USA were collected and tested by immunofluorescence assay against the spike and nucleocapsid proteins of all known human coronaviruses (HCoVs). Results: The prevalence of SARS-CoV-2 serological cross-reactivity was significantly higher in samples from SSA compared with the USA. Most of these cross-reactive samples cross-recognized the SARS-CoV-2 nucleocapsid protein and the spike proteins of other HCoVs. Nucleocapsid proteins from HCoV-NL63 and HCoV-229E were detected in most samples, thereby implicating prior exposure to these two HCoVs as the likely source of cross-reactive antibodies against SARS-CoV-2. Conclusion: The low incidences of SARS-CoV-2 infection and disease in SSA appear to be correlated with the pre-pandemic serological cross-recognition of HCoVs, which are substantially more prevalent in SSA than the USA.